2016
DOI: 10.1186/s12957-016-0979-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations between BRAFV600E and prognostic factors and poor outcomes in papillary thyroid carcinoma: a meta-analysis

Abstract: BackgroundThe objective of this study is to perform a meta-analysis to evaluate the associations between the BRAFV600E mutation status and aggressive clinicopathological features and poor prognostic factors in papillary thyroid cancer.MethodsA literature search was performed within the PubMed, MEDLINE, Web of Science databases, and EMBASE databases using the Medical Subject Headings and keywords from January 2003 to July 2015. Individual study-specific odds ratios and confidence intervals were calculated, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 76 publications
(26 reference statements)
9
94
0
5
Order By: Relevance
“…(6,10,) Although most of the studies proved a strong association between BRAF mutation and the high-risk clinicopathological features, there are studies that have failed to prove a significant association for which no definitive explanation could be given. (15)(16)(17)(18) Comparable to the previous studies, BRAF mutation was negative in multinodular goitre and diffuse thyromegaly in our study, which proves that it is highly specific for papillary carcinoma. This highlights the significance of using BRAF mutational analysis in fine needle aspiration specimens so as to decide on further management and to avoid unnecessary thyroidectomies.…”
Section: Discussionsupporting
confidence: 81%
“…(6,10,) Although most of the studies proved a strong association between BRAF mutation and the high-risk clinicopathological features, there are studies that have failed to prove a significant association for which no definitive explanation could be given. (15)(16)(17)(18) Comparable to the previous studies, BRAF mutation was negative in multinodular goitre and diffuse thyromegaly in our study, which proves that it is highly specific for papillary carcinoma. This highlights the significance of using BRAF mutational analysis in fine needle aspiration specimens so as to decide on further management and to avoid unnecessary thyroidectomies.…”
Section: Discussionsupporting
confidence: 81%
“…Molecular testing has been increasingly applied to guide subsequent management for patients with an equivocal thyroid FNA diagnosis. Interestingly, although there are some conflicting data in the literature, BRAF V600E–positive tumors are generally reported as being associated with more aggressive clinical disease . A recent meta‐analysis by Liu et al showed that in addition to a higher TNM stage, lymph node metastases and the recurrence status correlate with the presence of a BRAF V600E mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The BRAF mutations in PTCs, in particular the V600E, are associated with clinical‐pathological features of tumor aggressiveness, as advanced stage, extrathyroidal invasion, and regional lymph node metastasis. Moreover several studies demonstrated a correlation between BRAF V600E and a poorer overall survival . The use of BRAF V600E as a circulating marker could have important clinical application in the management of patients with thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This might allow the diagnosis of some patients with PTC with a less invasive test and help to identify patients with unrecognized postoperative minimal residual disease. Moreover, the detection of circulating BRAF V600E could provide information regarding resistance to treatment and tumor recurrence …”
Section: Introductionmentioning
confidence: 99%